Safety culture and power: Interactions between perceptions of safety culture, organisational hierarchy, and national culture. (January 2020) - Tear, Morgan J.; Reader, Tom W.; Shorrock, Steven; Kirwan, Barry
Highlights: Position within an organisation's hierarchy predicts workers' safety culture perceptions. National cultural values for power and hierarchy predict workers' safety culture perceptions. National culture exacerbates the difference in safety culture perceptions between staff. No evidence to suggest engineers' safety culture perceptions are affected by national context. Abstract: Practices that involve power dynamics are integral to maintaining organisational safety (e.g. speaking-up, challenging poor behaviour, admitting error, communicating on safety), and staff engagement in these is assumed to be shaped by perceptions of safety culture. These perceptions, in-turn, are associated with (1) positions within an organisational hierarchy (which makes power-related acts more or less threatening), and (2) societal values for power distance (e.g. challenging authority). With a sample of 13, 573 of air traffic control staff (controllers, engineers, administrative, and management) from 21 national air traffic providers, we reconfirm the observation that managers perceive safety culture more positively than frontline staff (hypothesis 1), and that workers in countries with established values for hierarchy and power report safety culture as less positive than those from countries with low power distance (hypothesis 2). We then, for the first time, examine the interaction between these two factors, and establish that differences in safety culture perceptions between those higher in the hierarchy (management) and those lower in the hierarchy (air traffic controllers and administrative staff) are exacerbated by national contexts for large power distance (hypothesis 3). The study contributes to the literature by theorising the role of power in safety culture theory, and its influence upon safety culture perceptions. Moving forward, safety culture research and interventions may benefit from considering how power exists and manifests at the level of superior-subordinate dynamics.